INTERNATIONAL DIMENSIONS OF THE RELIGIOUS CONFLICTS (Religious dialogue and cooperation, 2022)
Тhe New World Order cannot be understood without accounting for theroleand the impact of religion and religious organizations. Actually, compared to theperioduntil the end of the Cold War, much more attention is paid to the religion andnationalismissues today. From security point of view one of the reasons for such a situationis basedon the growing number and internationalisation of the religious issues andconflictsaround the world. This paper analyses why and how local religious conflicts arebecomingan international issue. It is clear that internationalization of domestic conflicts isnotunique to religious conflicts. However, religious conflicts are among those that havebeeninternationalized in past 30-years. In security aspect, the internationalizationprocessofthese conflicts is very important because of its serious impact on the conflict resolutionorescalation dynamics as well.
Keywords: religion; conflict; security; international relations